2011
DOI: 10.3346/jkms.2011.26.6.734
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Infections in Asymptomatic Food Handlers in Elementary Schools without Norovirus Outbreaks in Some Regions of Incheon, Korea

Abstract: Norovirus (NV) has caused large outbreaks of gastroenteritis in schools. Studies of NV epidemiology in schools related to NV outbreaks have been frequently reported. However, reports of that in schools without outbreaks are not found. Presently, NV molecular epidemiology surveillance was carried out in asymptomatic food handlers working at nonoutbreak elementary schools in Incheon, Korea, in March, April and December, 2009. NV prevalence was examined by real-time reverse transcription-PCR (RT-PCR) and the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…According to a previous study by Yu et al , 3.4% (26/776) of asymptomatic food handlers were positive for NoV in elementary schools with no NoV outbreaks. The study revealed that the infection source for NoV outbreaks may be related to asymptomatic food handlers (30) . Jeong et al also reported similar results.…”
Section: Food-borne Outbreak and Sporadic Casesmentioning
confidence: 96%
“…According to a previous study by Yu et al , 3.4% (26/776) of asymptomatic food handlers were positive for NoV in elementary schools with no NoV outbreaks. The study revealed that the infection source for NoV outbreaks may be related to asymptomatic food handlers (30) . Jeong et al also reported similar results.…”
Section: Food-borne Outbreak and Sporadic Casesmentioning
confidence: 96%
“…Most NoV outbreaks are caused by the GII/4 genotype (5,6). Several large NoV related outbreaks in hospitalized patients with AGE have been confirmed in Korea since 2003 (7)(8)(9).…”
mentioning
confidence: 99%
“…NoV infections frequently result from person-to-person transmission in cruise ships, restaurants, hotels, nursing homes, schools, and hospitals (3,4). In addition, NoVs have been detected in environmental samples as well as in contaminated foods such as oysters, shellfish, sandwiches, salads, and even ice (2,5).…”
mentioning
confidence: 99%